Level of commitment among the employees of the local government unit of Mayorga, Leyte. - Gallaron, Jovelyn (Tacloban City Jovelyn Gallaron, 2010)
Mayorga is a fifth class municipality in the Province of Leyte. The researches were interested in finding out the extent to which employees of the said municipality perceived their own level of commitment while household heads served as inter-raters. Employee commitment refers to the psychological bond of an employee to an organization, the strength of which depends on the degree of employee involvement, employee loyalty, and belief in the values of the organization. The study also identified the socio-economic and demographic characteristics of these employees and their relationship with the level of bureaucratic idealism.
This research was conducted in the municipality of Mayorga, Leyte from January 22, 2010 until January 31, 2010. The respondents of this study were determined using multi-stage sampling. They were composed of 110 municipal employees and 272 household heads.
Data were presented, analyzed, and interpreted with the use of mean, point-biserial, Eta, and R-value. Results showed that the employees perceived themselves as having high level of commitment. However, the household heads perceived the employees' level of commitment as average only. The researchers identified that the socio-demographic variables have no significant relationship with the level of commitment of employees as they perceived themselves and as perceived by the household heads.
The findings of the study are important as they provide a good perspective in understanding the state of the bureaucracy and employees of the municipality of Mayorga. With a level of commitment among employees we can expect better public service in the government bureaucracy.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science